Signal Integration during T Lymphocyte Activation and Function: Lessons from the Wiskott–Aldrich Syndrome - Cotta-de-Almeida, Vinicius; Dupré, Loïc; Guipouy, Delphine; Vasconcelos, Zilton (Frontiers in Immunology, 2015)
Over the last decades, research dedicated to the molecular and cellular mechanisms underlying Primary immunodeficiencies (PID) has helped to understand the etiology of many of these diseases and to develop novel therapeutic approaches. Beyond these aspects, PID are also studied because they offer invaluable natural genetic tools to dissect the human immune system. In this review, we highlight the research that has focused over the last 20 years on T lymphocytes from Wiskott-Aldrich syndrome (WAS) patients. WAS T lymphocytes are defective for the WAS protein (WASP), a regulator of actin cytoskeleton remodeling. Therefore, study of WAS T lymphocytes has helped to grasp that many steps of T lymphocyte activation and function depend on the crosstalk between membrane receptors and the actin cytoskeleton. These steps include motility, immunological synapse assembly, signaling, as well as the implementation of helper, regulatory and cytotoxic effector functions. The recent concept that WASP also works as a regulator of transcription within the nucleus is an illustration of the complexity of signal integration in T lymphocytes. Finally, this review will discuss how further study of WAS may contribute to solve novel challenges of T lymphocyte biology.